Assessing educational poverty: Insights into youth opportunities - Cristina Davino; Antonio De Falco; Rosa Fabbricatore; Rosaria Romano (PLoS ONE, 2026)
Educational opportunities (EO) are the main drivers for ensuring the balanced growth of future generations and a more prosperous future for the community. A lack or inadequacy of EO can lead to conditions of educational poverty. Despite its fundamental relevance, measuring this phenomenon is still an open challenge in the scientific community, given its complex and multidimensional nature and multiple connections with other aspects such as family background and cognitive and emotional development. The objective of this paper is to identify the main factors that may contribute to measuring educational poverty in terms of deprivation or lack of opportunities for youth aged 15–19. A pilot study of youth living in the city of Naples is proposed to test a conceptual model and to characterize groups of youth with different levels of educational poverty. Factor analysis was carried out to uncover the underlying dimensions regarding EO. The findings underscore the phenomenon’s three-dimensional aspect, encompassing the dimensions of Family , School , and Environment . Additionally, the study revealed the diversity among respondents about these three dimensions by exploiting a hierarchical cluster analysis. Results showed that family background, Italian grade, gender, and type of school are significantly related to the detected groups, providing valuable insights into the issue of educational poverty.